Role of Dental Adult Stem Cells in Regenerative Medicine - Gupta, Ambika S; Gupta, Siddharth; Singaraju, Sasidhar; Singaraju, Medhini (Journal of Orofacial Research, 2013)
Statement of problem: Stem cell biology is today one of the most exciting field of research with promising possibilities in all spheres of medical and dental science. Erupting tooth and its allied structures have emerged as a valuable source of adult stem cells. A lot of research is going on around the world in the field of regenerative medicine with the help of adult dental stem cells, but a comprehensive review is missing. Purpose: This article provides an overview of different types of adult stem cells that have been isolated from teeth, includingdental pulp stem cells (DPSCs), stem cells from human exfoliated deciduous teeth (SHEDs), periodontal ligament stem cells (PDLSCs), dental follicle progenitor stem cells (DFPCs),and stem cells from apical papilla (SCAPs) with their use in regenerative medicine. Materials and methods: The literature was acquired in a systematic search of the titles–DPSC, SHED, PDLSC, DFPC and SCAP on PubMed. Articles dealing with only regenerative medicine and in English language were selected for review. Results: A total of 1,211 articles were found on PubMed. The articles were then shortlisted according to the set criteria and a total of 53 articles were selected and the review was prepared. Conclusion: Dental adult stem cells have proved themselves to be of vast future use. Research has shown that these cells can differentiate into variety of cells, e.g. smooth muscle cells, adipocytes, chondrocytes, and neurons, etc. A cautious and systematic approach still needs to be adopted in embracing this technology.